Aggression, violence and abuse in peer groups. Application of a qualitative and multi-technique methodology with grade 7 students from C.A.B.A. public schools - Veccia, Teresa (2012)
Aggression, abuse and violence tend to occur with an increasing intensity in society. It comes about in a similar way within the school. In order to achieve a proper approach to this subject, these terms should be differentiated, not only in relation to their meanings, but also in the subjective evaluation that different actors make of it. We consider abuse and bullying in particular, as modes of violence that are usually muted and often go unnoticed by the eyes of adults. This paper unfolds the findings achieved from the implementation of focus groups with twelve and thirteen years old children, within a qualitative and multi-technique methodology. It will expose how children see, perceive, think and interpret this problem that concern them and it is derived from a specific type of conflict in their interpersonal relationships.